Racecraft the soul of inequality in American life - Fields, Karen E. (London Verso, 2014)
Most people assume that racism grows from a perception of human difference: the fact of race gives rise to the practice of racism. Sociologist Karen E. Fields and historian Barbara J. Fields argue otherwise: the practice of racism produces the illusion of race, through what they call "racecraft." And this phenomenon is intimately entwined with other forms of inequality in American life. So pervasive are the devices of racecraft in American history, economic doctrine, politics, and everyday thinking that the presence of racecraft itself goes unnoticed.
Keywords: Racism--United States--History.